1999
DOI: 10.1021/jm990038q
|View full text |Cite
|
Sign up to set email alerts
|

Quinuclidine Inhibitors of 2,3-Oxidosqualene Cyclase-Lanosterol Synthase:  Optimization from Lipid Profiles

Abstract: Novel 3-substituted quinuclidine inhibitors of cholesterol biosynthesis are reported. Compounds were optimized against oxidosqualene cyclase-lanosterol synthase (OSC) inhibition in vivo, rather than by the conventional optimization of structure-activity relationship information based on in vitro OSC inhibition. Thus, examination of HPLC lipid profiles from orally dosed rats showed cholesterol biosynthetic intermediates and whether cholesterol levels were reduced. A new substituted quinuclidine pharmacophore 18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 13 publications
1
19
0
Order By: Relevance
“…Naringenin is the aglycone of naringin, a naturally occurring flavanone glycoside obtained from citrus fruits and grapefruit. Naringenin hypocholesterolemic effect is due to the reduction of both HMGR and acyl CoA: cholesterol O-acyltransferase activities [36] . Discovery of isoflavones as HMGR inhibitors in soy food is very intriguing.…”
Section: Flavonoidsmentioning
confidence: 99%
“…Naringenin is the aglycone of naringin, a naturally occurring flavanone glycoside obtained from citrus fruits and grapefruit. Naringenin hypocholesterolemic effect is due to the reduction of both HMGR and acyl CoA: cholesterol O-acyltransferase activities [36] . Discovery of isoflavones as HMGR inhibitors in soy food is very intriguing.…”
Section: Flavonoidsmentioning
confidence: 99%
“…In fact, potentially dose-limiting toxicity might arise from the consequent reduced levels of isoprenoids, ubiquinone, and dolichols. Also the inhibition of enzymes downstream of the lanosterol biosynthesis has the potential to afford toxicity arising from the utilization (in place of cholesterol) of biosynthetic intermediates containing the full sterol ring system (21). As a whole, FDFT1, SQLE, and OSC could be relevant targets for antihypercholesterolemic drugs.…”
Section: Statins: Action Mechanisms and Effectsmentioning
confidence: 99%
“…A variety of OSC inhibitors have been reported bearing amines (49), quinuclidines (21), isoquinolines (50), a lipophilic residue (41). Among others, an interesting compound is U-18666A that inhibits OSC at concentrations higher than 0.5 mM; however, it induces cataracts in rats (51), It was shown to intercalate into a lens lipid model membrane.…”
Section: Oxidosqualene Cyclasementioning
confidence: 99%
“…It is worth mentioning here that after a large screening study of 700 quinuclidine derivatives [105] a few compounds were found to inhibit in vivo oxidosqualene cyclase -lanosterol synthase (OSC). These leads were optimized to produce selective OSC inhibitors such as compound 69 or 70 (Fig.…”
Section: Quinuclidine Derivativesmentioning
confidence: 99%